Delivering Resveratrol on the Buccal Mucosa Using Mucoadhesive Tablets: A Potential Treatment Strategy for Inflammatory Oral Lesions - Martins, Isadora C. F.; Raposo, Nadia Rezende Barbosa; Mockdeci, Hanny R.; Polonini, Hudson Caetano; de Oliveira Ferreira, Anderson; Fabri, Gisele Maria Campos; das Gracas Afonso Miranda Chaves, Maria (Current Drug Delivery, 2018)
Background: Resveratrol is a polyphenol that has gained momentum in therapeutics in the last few years. Objective: In this study, we hypothesised that resveratrol could act prophylactically and/or treat inflammatory lesions of the oral cavity after being delivered by two different formulations of buccal mucoadhesive tablets (F1 and F2, which differed in terms of viscosity agents used). Methods: This hypothesis was assessed through permeation studies, to verify diffusion of the drug through the buccal mucosa using a porcine model to predict human in vivo behaviour. Results: F2 (tablet with less viscosity agent) presented better permeation than F1, but the amount of drug that crossed the mucosa was still low compared to the amount retained within it (35.90 μg found in the receptor medium and 15.63 mg quantified within the mucosa). Conclusion: This accounted for a local effect rather than a systemic one, which is desirable for local processes, such as oral mucositis, lichen planus, erythema multiforme, nicotinic stomatitis, recurrent aphthous stomatitis, among others. In this sense, resveratrol-loaded mucoadhesive tablets appear to be a prominent alternative to prevent and/or cure inflammatory lesions of the oral cavity.
Keywords: oral absorption